(untitled) (Fiep Bulletin - online, 2016)
Depression is defined as a common response to health problems and is often a problem subdiagnosticado in patient population. People may become depressed as a result of injury or illness may be suffering due to a previous or loss can browse healthcare for treating somatic complaints, which constitute the bodily manifestations of depression. The objective of this study was to verify the prevalence of depressive disorders in elderly institutionalized and identify the factors that influence in the development of depression among this population group. Thisis a descriptivestudywith quanti-qualitative approach. The same study site had as an institution of long stay in alto sertãoparaibano. The data obtained were analyzed from the assessment of the Geriatric Depression scale and technique of speech Subject collective. The results showed that all study participants had some degree of depression and what factors as loneliness and death of loved ones directly influenced the development of such condition. This way, we emphasize the need for an ongoing evaluation of elderly residents in these institutions, by professionals qualified to identify potential affective disorders. Concluded on the basis of data obtained the studied population presents with a mild depression (90%) and only 10% has a severe depression. The factors that most influence in the development of depression are: lack of family structure, loneliness, death in the family, contempt of relatives, lack of a caregiver and financial difficulties.